Communicating with Consumers - Robert Ross (Journal of Applied Communications, 1970)
As I understand it, the American Association of Agricultural College Editors is composed of news writers, publication editors, radio and television broadcasters, and visual aids specialists at land grant universities, state agricultural experiment stations, and the U.S. Department of Agriculture.